2012
DOI: 10.2527/jas.2011-4209
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation reduces methane emission in beef cattle fed sugarcane-based diets1

Abstract: The objective of this study was to determine the effect of dietary nitrate on methane emission and rumen fermentation parameters in Nellore × Guzera (Bos indicus) beef cattle fed a sugarcane based diet. The experiment was conducted with 16 steers weighing 283 ± 49 kg (mean ± SD), 6 rumen cannulated and 10 intact steers, in a cross-over design. The animals were blocked according to BW and presence or absence of rumen cannula and randomly allocated to either the nitrate diet (22 g nitrate/kg DM) or the control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
88
4
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 26 publications
34
88
4
14
Order By: Relevance
“…No individual MetHb measurement was >15% of total Hb which was substantially <30% total Hb, the value associated with clinical symptoms of methaemoglobinemia (Bruning-Fann and Kaneene, 1993). This agrees with most studies in which animals were adapted slowly to dietary nitrate by increasing nitrate intakes over a period of weeks (cattle:, Hulshof et al, 2012;Van Zijderveld et al, 2011 andsheep: Li et al, 2012;Van Zijderveld et al, 2010). Slow adaptation to dietary nitrate allows the rate of reduction of nitrite to ammonia by the rumen microflora to increase and prevents accumulation of nitrite in the rumen and absorption from the rumen and thereby avoids conversion of haemoglobin to MetHb (Lee and Beauchemin, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No individual MetHb measurement was >15% of total Hb which was substantially <30% total Hb, the value associated with clinical symptoms of methaemoglobinemia (Bruning-Fann and Kaneene, 1993). This agrees with most studies in which animals were adapted slowly to dietary nitrate by increasing nitrate intakes over a period of weeks (cattle:, Hulshof et al, 2012;Van Zijderveld et al, 2011 andsheep: Li et al, 2012;Van Zijderveld et al, 2010). Slow adaptation to dietary nitrate allows the rate of reduction of nitrite to ammonia by the rumen microflora to increase and prevents accumulation of nitrite in the rumen and absorption from the rumen and thereby avoids conversion of haemoglobin to MetHb (Lee and Beauchemin, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…However, a comprehensive review by Bruning-Fann and Kaneene (1993) reported a reduction in feed intake when nitrate was included in the diet at 10 g nitrate/kg DM (cattle) and 30 g nitrate/kg DM (sheep). In agreement, Hulshof et al (2012) reported a tendency for calcium nitrate (fed at 22 g nitrate/kg DM) to reduce DMI by 6% in beef cattle fed a sugarcane-based diet. In contrast, Sangkhom et al (2012) reported improved growth rates and feed conversion efficiency in growing cattle when potassium nitrate (fed at C-A.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recent research on sheep (Sar et al, 2004;Nolan et al, 2010;van Zijderveld et al, 2010) and cattle (van Zijderveld et al, 2011a and2011b;Hulshof et al, 2012) has shown promising results with nitrates decreasing enteric CH 4 production by up to 50%. Nitrates may be particularly attractive in developing countries where forages contain negligible levels of nitrate and insufficient CP for maintaining animal production.…”
mentioning
confidence: 99%
“…During the last two decades, calorimeter data from research institutes has been used to develop a range of prediction models to facilitate an improved understanding of the effects of diet and animal factors on enteric CH 4 emissions (Mills et al, 2003;Yan et al, 2010;Ellis et al, 2012). In addition, many nutritional strategies designed to reduce CH 4 emissions at an individual animal basis have been evaluated, including the use of dietary manipulation (e.g., improving forage quality, inclusion of concentrates, feed processing) and dietary additives (e.g., inhibitors, electron receptors, ionophores, plant bioactive compounds) (Hulshof et al, 2012;Hristov et al, 2013;Ramin and Huhtanen, 2013). Although some of these 'additive' and 'biotechnological' approaches are promising, their long-term effects have not yet been extensively established.…”
Section: Introductionmentioning
confidence: 99%